ЭПИКАЛЫҚ ЖАНР ТИПОЛОГИЯСЫ - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2021)
This article examines the typology of twentieth-century Karakalpak prose. Literary types and genres in the field of literary criticism were studied by G.L.Abramovich, L.I.Timofeev, G.N.Pospelov, V.E.Khalizev, Karakalpak scholars S.Akhmetov, K.Sultanov, K.Mambetov. K.Zharimbetov’s comments on the term of the epic genre are given. The historical sources of the narrative genre, the ways of its formation have been studied. The epic genres created by Karakalpak writers S.Mazhitov, A.Begimov, J.Aimurzaev, K.Sultanov, T.Kaipbergenov in the national literature are analyzed. It also covers the views of scholars who have studied Karakalpak prose M.K.Nurmukhamedov, Zh.Narymbetov, S.Bahadyrova on the research work on the typology of the Karakalpak novel.